2004
DOI: 10.1158/1078-0432.ccr-04-0721
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model of Human Myelotoxicity Using Five Camptothecin Derivatives and the In vitro Colony-Forming Unit Granulocyte/Macrophage Assay

Abstract: Purpose: Many promising anticancer drugs are limited by myelosuppression. It is difficult to evaluate human myelotoxicity before a Phase I study because of the susceptibility of humans and animals to hematotoxicity. The purpose of this study was to establish a reliable method to predict the human maximum tolerated dose (MTD) of five camptothecin derivatives: SN-38, DX-8951f, topotecan, 9-aminocamptothecin, and camptothecin.Experimental Design: The myelotoxicity of SN-38 and DX-8951f were evaluated on bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Although human and canine bone marrow may have similar sensitivity to TopoI inhibitors, we found that murine bone marrow is 4.5-to 27-fold less sensitive to these compounds. The differential sensitivity between murine and human bone marrow progenitor cells to TopoI inhibitors may explain, in part, why curative doses/blood levels of topotecan and irinotecan/SN-38 in mice with human tumor xenografts are not achievable in patients (51,52). The corollary is that compounds with smaller or no differential in bone marrow progenitor sensitivity among species would likely have a better potential for reaching similar blood levels in patients as in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although human and canine bone marrow may have similar sensitivity to TopoI inhibitors, we found that murine bone marrow is 4.5-to 27-fold less sensitive to these compounds. The differential sensitivity between murine and human bone marrow progenitor cells to TopoI inhibitors may explain, in part, why curative doses/blood levels of topotecan and irinotecan/SN-38 in mice with human tumor xenografts are not achievable in patients (51,52). The corollary is that compounds with smaller or no differential in bone marrow progenitor sensitivity among species would likely have a better potential for reaching similar blood levels in patients as in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Top1 inhibitors kill rapidly dividing bone marrow progenitor cells and tumor cells, resulting in acute reversible neutropenia and thrombocytopenia 4 to 20 days after administration (18). Bone marrow colony-forming unit-granulocyte macrophage (CFU-GM) assays comparing the sensitivity of bone marrow cells across species are useful in predicting the blood levels of an agent that might be achieved with acceptable toxicity in patients (18)(19)(20)(21). In general, murine bone marrow has a lower sensitivity to Top I inhibitors than does human bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these observations, it has been suggested that compounds with little differential in bone marrow sensitivity across species may have greater potential for reaching similar blood levels in patients as in mice (25). So, on the basis of the CFU-GM assay developed by Pessina and colleagues (46) and validated in several studies (26,47,48), we demonstrated that the mouse bone marrow is only about 5-fold less sensitive than human bone marrow, thus suggesting that EMICORON could reach a similar blood levels in humans as in mice. This is in line Real-time tumor dissemination was monitored by the imaging system.…”
Section: Discussionmentioning
confidence: 99%